Verbal bullying 101: Words that wound in the discourse of bullying according to Dhar Mann's videos - Susanti, Allycia; Agna, Sukma Kirani (Department of Applied Linguistics, FBSB, Universitas Negeri Yogyakarta, 2023)
This paper analyses media portrayals of verbal bullying, including its definition, types, and its negative consequences on both the victims and perpetrators, through the lens of Dhar Mann videos. Bullying can be physical, verbal, or relational, and is usually repetitive and involves a power imbalance between the perpetrator and the victim. This paper highlights that the media plays a significant role in shaping the public perception of bullying, and the issue has gained traction through mass media platforms such as YouTube. YouTube has become one of the most famous platforms for establishing current news, entertainment, and educational materials. This paper analyzes the videos that were uploaded to the Dhar Mann YouTube channel, a well-known channel which posts inspirational videos that aim to teach moral lessons. This study reveals that Dhar Mann's videos exhibited different types of verbal bullying and how they occur. Six Dhar Mann videos were chosen and were analysed using a qualitative analysis involving code-scheming and narrative analysis using Krippendorff's (2018) content analysis framework. It can be concluded that verbal bullying can be classified into taunting, insulting, threatening, blaming, and name-calling. This analysis is expected to establish the foundation for future studies on verbal bullying discourse.